A new Backstepping Sliding Mode Controller applied to a DC-DC Boost Converter - Yosra Massaoudi; Dorsaf Elleuch; Jean Paul Gaubert; Driss Mehdi; Tarak Damak (Institute of Advanced Engineering and Science, 2016)
In order to deal with the boost converter non minimum phase property and to solve the Sliding Mode Control (SMC) major problem (the chattering phenomenon), a new backstepping Sliding Mode Controller is developed. In this paper, a comparative study between the proposed controller and the (2-SMC)super twisting and the classical SMC is provided in order to evaluate each controller. Simulations and experimental results show the effectiveness and the robustness of the proposed controller with respect to load variation.